Evidence-Based Medicine - A Paradigm Ready To Be Challenged? How Scientific Evidence Shapes Our Understanding And Use Of Medicine - Schulte, Marie-Caroline (Springer Nature, 2020)
This open access book aims to clarify the term "evidence-based medicine" (EBM) from a philosophy of science perspective. The author, Marie-Caroline Schulte discusses the importance of evi-dence in medical research and practice with a focus on the ethical and methodological prob-lems of EBM. The claims that EBM can herald a new theory of epistemology and a Kuhnian paradigm will be refuted. The solution is to describe EBM as a necessary development in medicine to deal with the increasing amount of evidence and medical data without loosing the single patient out of sight. ​